H. J. van Eikema Hommes, Major Trends in the History of Legal Philosophy - Czarnota, Adam (Czasopismo Prawno-Historyczne, 1983)
Recenzja: H. J. van Eikema Hommes, Major Trends in the History of Legal Philosophy, Amsterdam—New Jork—Oxford 1979, North-Holland Publishing Company, ss. 442.